The Role of Ethics, Public Service Quality, and Bureaucratic Reform in Integrity Zone Implementation - Sullaida; Khairawati; Azhar Hasan (Global Research Collaboration, 2026)
This study examines the effects of ethics, public service quality, and bureaucratic reform on integrity zone implementation in a public sector organization. Integrity zone implementation is conceptualized not merely as an administrative designation, but as an institutional transformation process that depends on ethical conduct, service quality, internal accountability, and sustained reform efforts. The study employs a quantitative explanatory design using survey data collected from employees in a government institution. Primary data were obtained through structured questionnaires and analyzed using multiple linear regression with the support of SPSS. The findings indicate that ethics, public service quality, and bureaucratic reform each have a positive and significant effect on integrity zone implementation, both individually and collectively. These results suggest that integrity zone implementation is shaped by the interaction between individual ethical commitment, the quality of public service delivery, and the consistency of bureaucratic reform. The study highlights that strengthening integrity zone implementation requires more than formal compliance, as it also depends on the internalization of ethical values, service standardization, adherence to standard operating procedures, performance monitoring, and the development of a professional and accountable organizational culture. This study contributes to the public administration literature by offering empirical evidence on how ethics, service quality, and reform capacity jointly support institutional integrity in the public sector.